Predicting disaggregated tourist arrivals in Sierra Leone using ARIMA model - Emerson Abraham Jackson; Edmund Tamuke (ZBW – Leibniz Information Centre for Economics, 2019)
This study have uniquely mad use of Box-Jenkins ARIMA models to address the core of the threes objectives set out in view of the focus to add meaningful value to knowledge exploration. The outcome of the research have testify the achievements of this through successful nine months out-of-sample forecasts produced from the program codes, with indicating best model choices from the empirical estimation. In addition, the results also provide description of risks produced from the uncertainty Fan Chart, which clearly outlined possible downside and upside risks to tourist visitations in the country. In the conclusion, it was suggested that downside risks to the low level tourist arrival can be managed through collaboration between authorities concerned with the management of tourist arrivals in the country. – – Cette étude utilise de manière particulièrement insensée les modèles ARIMA de Box-Jenkins pour répondre au cœur des trois objectifs définis en vue d'ajouter une valeur significative à l'exploration du savoir. Les résultats de la recherche témoignent des résultats obtenus grâce aux prévisions hors échantillons de neuf mois obtenues avec succès par les codes de programme, en indiquant les meilleurs choix de modèle à partir de l'estimation empirique. En outre, les résultats fournissent également une description des risques issus du graphique d'incertitude relatif à l'incertitude, qui décrit clairement les risques potentiels de baisse et de hausse pour les touristes en visite dans le pays. En conclusion, il a été suggéré que les autorités concernées par la gestion des arrivées de touristes dans le pays puissent gérer les risques liés aux arrivées de touristes de faible niveau.
Keywords: C32; C52; C53; L83; 330; ARIMA Methodology; Out-of-Sample Forecast; Tourist Arrivals; Sierra Leone